PELATIHAN PERSIAPAN MEMASUKI MASA PUBERTAS BAGI SISWA SEKOLAH DASAR NEGERI 69 KOTA BENGKULU - Rita Sinthia; Mona Ardina; Yessy Elita (Universitas Bengkulu, 2018)
This activity was conducted to prepare elementary school students, particularly the fifth and sixth grade students of SDN 69 Kota Bengkulu in entering puberty period. Puberty is the period development during, when the children from being regarded as asexual creatures to being extremely sexual. The experience of puberty period of children is characterized by primary sex characteristics, where the girls will experience first menstruation period. While some boys experience wet dream. According the result of observation and interview towards students, many students could not figure out what puberty is. The data show that the students do not acquire enough knowledge about what they will experience in puberty period. It may causes the students create poor attitude toward puberty period such as; shock even depressed and profoundly ashamed. That’s why the students need guide in aware puberty period in order to be able to face puberty period in physical change as well as emotional change. This activity wasparticipated by 43 students. The method of this research was lecture and fun discussion. The result of this activity shows that the students have understanding of puberty, and they are supposed to be able to know how to deal with puberty period, thus they are able to do the development tasks in this stage as it should be. Keywords: preparation, puberty, elementary school students